STUDY THE EFFECT OF CHANDANBALALAKSHADI TAILA PICHU IN PARIKARTIKA WITH SPECIAL REFERENCE TO FISSURE-IN-ANO: A PILOT STUDY - Yogesh Badwe; Kalyani Pendam (AYUSHDHARA, 2020)
Parikartika i.e. Fissure-in-ano is the most common disease amongst anorectal disorders. In this condition, there is severe cutting type of pain at anal region with a longitudinal ulcer at anal margin. Modern treatment includes local application of soothing ointments, oral analgesics and stool softeners in initial condition. Surgical management includes Lord’s dilation, fissurectomy and sphincterotomy. But these treatments are with the fear of some complications like recurrence, incontinence. It is a need to find an alternative and better treatment to treat the diseases like Parikartika. To treat Fissure-in-ano, two important things are important, in which one is to reduce burning pain at anal region and another is to heal the longitudinal ulcer. Keeping these aspects in mind, a pilot study was conducted using local application of Chandanbalalakshadi Taila Pichu in the treatment of Parikartika w.s.r. to fissure-in-ano. Methodology: A total 15 patients of Parikartika (Fissure- in- ano) were selected for local application of Chandanbalalakshadi Taila Pichu in fissure bed twice a day after sitz bath for 21 days. Result: Very encouraging effects of local application of Chandanbalalakshadi Taila Pichu were noted. Pain at anal region, wound at anal region, spasm and bleeding per rectum were significantly reduced. Considering overall effect out of 15 patients 8 patients of Fissure-in-ano were completely cure i.e., 53.3% and 7 patients were markedly improved i.e. 46.7%. Conclusion: Considering all above properties of individuals drugs, observations and results it can be said that Chandanbalalakshadi Taila is useful in reducing pain, inflammation, spasm and bleeding per rectum and healing of wound at anal region. Hence, it can be concluded that this oil is useful in the treatment of Parikarika (fissure-in-ano).